Credit Risk Management Practices and Sustainability of Saccos - Jackline Abarinde (Uganda Christian University, 2023)
The study assessed the influence of credit risk management on sustainability of jubilee SACCO in Bushenyi district. It was guided by the following specific objectives : To ascertain the influence of Credit management policies on sustainability of Jubilee SACCO, To assess the impact of Appraisal of Loan Borrowers on sustainability of Jubilee SACCO and to The establish the Loan recovery challenges at Jubilee SACCO. The study adapted descriptive research design with both quantitative and qualitative approaches. The data was analyzed using descriptive statistics and thematic analysis. The study population was 78 and the sample size was 68. The study established that the positive effects of credit management policies of sustainability Jubilee SACCOs were: assessment of the credit worthiness of a borrower at jubilee SACCO, the policy framework at Jubilee SACCO provides for Credit Risk identification for effective risk management. It was also revealed that at jubilee loan portfolio management is government by policies established by the members and the board. The SACCO has adopted various approaches in screening and analyzing risk before awarding credit to client to minimize loan loss, Governance structures ensured that the laid down credit risk policies are strictly adhered to at the SACCOs, Appraisal of borrowers promoted sustainability of the SACCCO, and Screening borrowers at Jubilee SACCO reduced the PaR,. The study concluded that Jubilee SACCO management needs to address credit risk challenges in order to prevent it from failing in its obligation and meeting its objective, minimize loan defaulters, cash loss and ensures the organization performs better increasing the return on assets and helping the organization in attaining maximum financial returns. The study further concludes that the SACCO considers risk identification process in credit risk management as essential in optimizing financial performance.
This is a dissertation.